Connecting the Dots - Altintas Kaptan, Meric; Ünlü, Aslıhan; Pottgiesser, Uta (Journal / DOCOMOMO, International Working Party for Documentation and Conservation of Buildings, Sites and Neighbourhoods of the Modern Movement)
The Modern Movement encompasses a diverse collection of both iconic and ordinary treasures of architecture worldwide, among which some are safeguarded with respect to their values, while others were demolished, have undergone alterations, neglect, or lack of maintenance and preservation over time. Docomomo has been playing a pivotal role in documenting and safeguarding significant architectural works of the 20th century. Its National and Regional Working Parties (WPs), spread across the globe, have diligently compiled archives of photographs, drawings, historical records, and research materials related to Modern Movement architecture, town planning and landscape design. However, the decentralized nature of these archives poses challenges in terms of accessibility, coordination, and attaining a more comprehensive record of the Modern Movement with a global perspective. Therefore, this study undertakes the explorative task of compiling data from these separate online-available archives of the WPs to attain a broader overview of the documented objects of Modern Movement architecture on a global-scale. The collected data is analyzed to identify patterns, trends, and influential architects and to elaborate on the potential factors contributing to the current status. The study involves analysis of the predominant format of building use/function among documented architectural works, examination of the geographical and chronological coverage of available lists, and the distribution of intervention status within the inventory. These aspects provide valuable insights into the functional diversity, geographic spread, and preservation status of architectural works documented in the dispersed archives. This study also facilitates comparative studies between different regions and countries, shedding light on the shared characteristics and unique contributions of the Modern Movement across diverse cultural contexts. The results help identify trends, gaps, and areas of focus for future research and documentation efforts, ensuring the holistic appreciation of architectural works, and contributing to the scholarly understanding and preservation of this modern heritage.
Keywords: Urban Studies; Architecture; Heritage